Strongly bonded water monomers on the ice Ih basal plane: Density-functional calculations - Thierfelder, C.; Hermann, A.; Schwerdtfeger, P.; Schmidt, Wolf Gero (Physical Review B)

Adsorption of water on chlorine-terminated Si(111) from first principles: Substrate-induced ordering versus intermolecular interactions - Biering, S.; Hermann, A.; Schmidt, Wolf Gero (Physical Review B)

Ga-richGaAs(001)surface fromab initiocalculations: Atomic structure of the(4×6)and(6×6)reconstructions - Seino, K.; Schmidt, Wolf Gero; Ohtake, A. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Semiempirical van der Waals correction to the density functional description of solids and molecular structures - Ortmann, F.; Bechstedt, F.; Schmidt, Wolf Gero (Physical Review B)

Temporal decay of coherently optically injected charge and spin currents due to carrier–LO-phonon and carrier-carrier scattering - Duc, H. T.; Vu, Q. T.; Meier, Torsten; Haug, H.; Koch, S. W. (Physical Review B)
The coherent ultrafast optical injection and the temporal evolution of charge and spin currents in semiconductors is analyzed using a microscopic many-body theory. The approach is based on the semiconductor Bloch equations and includes light-field-induced intraband and interband excitations, excitonic effects, and carrier–LO-phonon and carrier-carrier scattering processes. The relaxation effects are treated both in the second Born-Markov approximation and on the level of quantum kinetic theory including memory effects. The dynamics of the charge and spin currents is evaluated numerically for a one-dimensional model system. The dependence of the currents and their decay on the temperature, the excitation intensities, and the frequencies of the incident light fields is discussed. Whereas the overall decay dynamics is described well within the Markov approximation, the quantum kinetic theory predicts additional oscillatory signatures in the current transients.

Thermal stability of magnetic nanostructures in ion-bombardment-modified exchange-bias systems - Höink, V.; Sacher, Marc; Schmalhorst, J.; Reiss, G.; Engel, D.; Weis, T.; Ehresmann, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Exciton dephasing via phonon interactions in InAs quantum dots: Dependence on quantum confinement - Borri, P.; Langbein, W.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Optical orientation of electron spins in GaAs quantum wells - Pfalz, S.; Winkler, R.; Nowitzki, T.; Reuter, Dirk; Wieck, A. D.; Hägele, D.; Oestreich, M. (Physical Review B)

Ultrafast electron-phonon interaction of intersubband transitions: Quantum kinetics from adiabatic following to Rabi-oscillations - Butscher, Stefan; Förstner, Jens; Waldmüller, Inès; Knorr, Andreas (Physical Review B)
The interaction of electrons with LO phonons provides an important mechanism of optical dephasing and carrier scattering for the two-dimensional electron gas in semiconductor quantum wells. In this paper, the corresponding ultrafast nonlinearities for off-resonant and resonant intersubband excitations are investigated. Quantum kinetic effects of the electron-phonon interaction and the corresponding violation of the microscopic energy conservation yield a qualitative different picture compared to the standard Markovian theory, if the phonon energy is larger than the intersubband-gap energy.
Keywords: tet_topic_qw